THE PERCEPTIONS OF STUDENTS TOWARDS YOUTUBE VIDEO IN PRONUNCIATION - Mulyani; Sariakin; syarfuni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims at exploring the EFL students’ perceptions towards the use of YouTube video media in learning English pronunciation whether positive or negative. This study employs a mixed-methods approach using questionnaire and observation sheet to 28 students from one of junior high schools in Aceh Besar, Aceh. Therefore, based on the results of the questionnaire, it can be stated that the majority of students responded very positively to the use of YouTube-based video media. Based on the results of observation, it indicated that the majority of students showed a very good assessment in terms the students’ interest, the atmosphere of learning in class, as well as the activeness and involvement of the students through the use of YouTube video media. This is indicated by the high percentage of all statements on the aspects of students' interest in the use of the media in learning pronunciation. Thus, there is a positive significant result shown by the EFL students towards the use of YouTube video media in learning English pronunciation